Estimation of abdominal subcutaneous fat volume of obese adults from single-slice MRI data – Regression coefficients and agreement. Issue 130 (September 2020) - Linder, Nicolas; Michel, Sophia; Eggebrecht, Tobias; Schaudinn, Alexander; Blüher, Matthias; Dietrich, Arne; Denecke, Timm; Busse, Harald
Highlights: Abdominal subcutaneous fat volume is a promising non-invasive marker of obesity. Slice-based estimation by MRI or CT is common and feasible but poorly standardized. Coefficients of regression and determination have been determined systematically. Disc spaces L5/S1, L4/L5 or the umbilicus are superior to other single-slice landmarks. Extension to five slices yielded a moderate improvement of the accuracy only. Abstract: Purpose: Cross-sectional imaging is increasingly used to quantify adipose tissue compartments in subjects with overweight or obesity. The lack of ionizing radiation makes magnetic resonance imaging (MRI) highly preferable to computed tomography (CT) although it is generally less standardized and time-consuming. Fat areas of single or stacks of neighboring slices have previously been considered as surrogates to avoid laborious processing of whole abdominal data–but studies are inconsistent in design and results. The present work therefore analyzed a relatively large number of overweight or obese adults and involved a total of eight landmarks and two surrogates (slice and stack). The goals were to identify the most reliable estimators of abdominal subcutaneous adipose tissue (ASAT) volume for both genders and to relate the findings to the pertinent literature. Material and methods: Anthropometric and fat-sensitive 1.5 T MRI data of 193 patients (116 female, 77 male) from different IRB-approved studies at a single clinical research institution (IFB Adiposity Diseases, University Medicine Leipzig, Germany) were analyzed retrospectively. Mean (± SD) age and BMI were 51.5 (± 12.4) years and 33.7 (± 3.9) kg/m 2 for females versus 57.6 (± 12.4) years and 32.1 (± 3.7) kg/m 2 for males. Areas of selected axial slices (10 mm thick, 0.5 mm gap) and of stacks of five slices at common landmarks – intervertebral disc spaces L1/L2 to L5/S1, anterior superior iliac spine (ASIS), femoral head (FH) and umbilicus (UM) – were considered as estimators for ASAT volume (reference). Agreement between simple areas and reference volumes was asssessed by linear regression (coefficient of determination R 2 ) as well as standard deviations of percent differences s d% between estimated and measured volumes. Results: ASAT volumes ranged from 6.61 to 21.94 L for females (mean: 13.37 L) and from 5.42 to 17.90 L (mean: 9.89 L) for males. The smallest s d% (8.4 %–10.1 %) and largest R 2 values (0.86–0.92) for single slices were observed for three candidate slice positions that were also associated with the highest ASAT volume fraction: L4/L5, L5/S1 and UM. The stack estimates for these landmarks were overall somewhat better (7.3 %–9.7 %, 0.88–0.94, respectively). The differences in s d% between genders ranged between 0.2 % and 1.1 %. Conclusion: ASAT volume in overweight or obese patients can be readily estimated with good accuracy from a single MRI slice centered at intervertebral disc space L5/S1 for both genders. Disc space L4/L5 or the umbilicus are nearly equivalent landmarks, in particular for male subjects. The extension to stack measures may yield too little improvement to justify the extra effort. Landmarks like ASIS, FH or the remaining lumbar disc spaces are considered as unreliable.